Fundamental information in technical trading strategies - Ute Boonenkamp; Alexander Kempf; Carsten Homburg (University of Cologne, Centre for Financial Research (CFR), 2009)
Technical trading strategies assume that past changes in prices help predict future changes. This makes sense if the past price trend reflects fundamental information that has not yet been fully incorporated in the current price. However, if the past price trend only reflects temporary pricing pressures, the technical trading strategy is doomed to fail. We demonstrate that this failure can be avoided by using financial statements as additional sources of information. We implement a trading strategy that invests in stocks with high past returns and high operating cash flows. This combination strategy yields a 3-factor alpha of 15% per year, which is much higher than that of the pure momentum strategy that invests in stocks with high past returns without considering operating cash flows. The combination strategy outperforms the momentum strategy in almost all years. The outperformance can be traced back to a higher probability of picking outperforming stocks. These are stocks that yield high future cash flows and hardly ever delist due to poor performance. The combination strategy is easily implemented: the information used is publicly available, the stocks chosen are liquid, and even high transaction costs do not erode the outperformance.
Keywords: G11; G12; G14; 330; Wertpapierhandel; Anlageverhalten; Börsenkurs; Börsen-Informationssystem